Calves Productivity with Applying Integrated Village Management System (IVMS) and Rice-Straw Based Feed - Ratnawati, Dian; Dikman, Dicky Mohammad; Affandhy, Lukman (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The objective of the study was to assess the productivity of PO calves with Integrated Village Management System (IVMS). The calf management generally follows cow pattern. Â The IVMS management applied to calves include weaning 5-6 months and optimizing local feed. Straw-based cow feed with supplementation using greenfeed and concentrate. Recording productivity of calf include: birth, weaning, body weight, calf death calf mobilization. Weighing weight was done at birth, weaning, and every month in the first year of study and every 2 months in the next research year. Implementation of IVMS management with rice straw-based feed produces good PO calf productivity when supported by addition of other feed sources, i. e. feed with high protein composition (concentrate, legume) to balancing the nutrient composition of feed.